Tendon and ligament mechanical loading in the pathogenesis of inflammatory arthritis - Gracey, Eric; Burssens, Arne; Cambre, Isabelle; Schett, Georg; Lories, Rik; Mcinnes, Iain B.; Asahara, Hiroshi; Elewaut, Dirk (Nature Reviews Rheumatology, 2020)
Mechanical loading is an important factor in musculoskeletal health and disease. Tendons and ligaments require physiological levels of mechanical loading to develop and maintain their tissue architecture, a process that is achieved at the cellular level through mechanotransduction-mediated fine tuning of the extracellular matrix by tendon and ligament stromal cells. Pathological levels of force represent a biological (mechanical) stress that elicits an immune system-mediated tissue repair pathway in tendons and ligaments. The biomechanics and mechanobiology of tendons and ligaments form the basis for understanding how such tissues sense and respond to mechanical force, and the anatomical extent of several mechanical stress-related disorders in tendons and ligaments overlaps with that of chronic inflammatory arthritis in joints. The role of mechanical stress in ‘overuse’ injuries, such as tendinopathy, has long been known, but mechanical stress is now also emerging as a possible trigger for some forms of chronic inflammatory arthritis, including spondyloarthritis and rheumatoid arthritis. Thus, seemingly diverse diseases of the musculoskeletal system might have similar mechanisms of immunopathogenesis owing to conserved responses to mechanical stress.
CRIS-Team Scopus Importer:2020-03-06